Comparative efficacy and safety of intra-articular analgesics after knee arthroscopy: a Bayesian network meta-analysis protocol. Issue 9 (17th September 2020) - He, Yuchen; He, Hongyi; Xie, Dong-Xing; Li, Xiaoxiao; Wang, Yilun
Abstract : Introduction: Most of the patients who received arthroscopic knee surgery will suffer moderate to severe pain, which can delay the rehabilitation process and increase the risk of postoperative complications. Therefore, seeking a safe and effective postoperative analgesia is necessary for promoting the application of arthroscopic surgery. This protocol aims to detail a planned systematic review and meta-analysis on the comparative efficacy and safety of single-dose intra-articular injection of analgesics for pain relief after knee arthroscopy. Method and analysis: PubMed, Embase, Web of Science and Cochrane Library will be searched from inception to 1 June 2020 to retrieve randomised controlled trials (RCTs) that compared the commonly used single-dose intra-articular analgesics (ie, morphine; bupivacaine (including levobupivacaine); ropivacaine and magnesium alone or in combination) with placebo or between each other for postoperative pain relief among patients who had received knee arthroscopy. The primary outcome is pain intensity at 2-hour and 24-hour postoperatively; the secondary outcomes include side effects (eg, knee effusion, nausea, vomiting and flushing), the number of patients requiring supplementary analgesia and the time to first analgesic request. The methodological quality of the included RCTs will be assessed based on the Cochrane risk of bias table. The Bayesian network meta-analysis will be conducted using WinBUGS V.1.4.3. Ethics and dissemination: Since no private or confidential patient data will be contained in the reporting, approval from an ethics committee is not required. Our study raises no ethical issue, and the results will be published in a peer-reviewed journal. PROSPERO registration number: CRD42019130876.